Determinants of stroke following percutaneous coronary intervention in patients with acute coronary syndrome: a systematic review and meta-analysis - Andriany Qanitha; Abdul Hakim Alkatiri; Nurul Qalby; Gita Vita Soraya; Muhammad Azka Alatsari; Nabilah Puteri Larassaphira; Rif'at Hanifah; Peter Kabo; Muzakkir Amir (Annals of Medicine)
Background Despite advances in the field, no systematic review has thoroughly documented the occurrence of stroke following Percutaneous Coronary Intervention (PCI) in patients with Acute Coronary Syndrome (ACS). This study aimed to investigate the factors contributing to stroke occurrence post-PCI in ACS patients.Methods A systematic search of PubMed and EMBASE identified 2,369 articles. After full-text screening, 109 articles were included in the systematic review, with 55 articles selected for meta-analysis.Results Data from 18,466,823 patients across 109 studies were analyzed. Among these, 202,999 patients (1.1%) experienced post-PCI stroke. The participants' ages ranged from 49.0 to 87.6 years (mean 64.3 ± 6.2 years). The incidence of early post-PCI stroke within 30 days was 1.1%, while the incidence of stroke occurring >30 days post-PCI was 1.8%, predominantly ischemic strokes. Predictors of stroke following PCI in ACS patients included traditional risk factors (i.e. female sex, older age, diabetes mellitus, hypertension, prior stroke or transient ischemic attack); comorbidities (i.e. chronic kidney disease, atrial fibrillation, anemia, high bleeding risk); and procedural factors (i.e. thrombus aspiration and Clopidogrel use).Conclusions This study highlights the relatively low prevalence of stroke following PCI, estimated at approximately 1% of the studied population. These findings emphasize the critical need for continued vigilance in identifying and managing risk factors associated with post-PCI stroke in ACS patients. Future research should prioritize refining risk prediction models, developing innovative preventive strategies, and optimizing post-PCI care pathways to effectively reduce the incidence of stroke in this population.